Wind Lidar Applicability in Low Visibility Weather in Qingdao - Yan Shen; Shi Xiaomeng; Fu Gang; Chen Qingfeng; Li Yuwei (应用气象学报)
Utilizing data of Doppler wind lidar and L-band radiosonde system installed at Qingdao National Basic Meteorological Observing Station from April 2021 to December 2022, their detection capability and accuracy under low visibility weather conditions are compared and evaluated, specifically in terms of detection height, horizontal wind speed and wind direction, using data obtained from L-band radiosonde system as the reference standard. During non-precipitation weather, when visibility exceeds 10000 m, the wind lidar demonstrates a stable average maximum detection height of approximately 1200 m. The root mean square errors of the wind speed and direction fluctuate around 1.2 m·s-1 and 25°, respectively. However, when the visibility drops below 10000 m, the detection height and accuracy of the wind lidar are influenced by the level of interference, particularly in different visibility and relative humidity ranges. In situations where visibility is below 1000 m, the decrease in atmospheric visibility is attributed to increased water vapor content in the air, with relative humidity consistently exceeding 95%. This high humidity significantly interferes with laser transmission in the atmosphere, resulting in an average maximum detection height of less than 400 m. The correlation between horizontal wind speed and direction decreases to 0.91 and 0.94, and the root mean square error increases to 1.4 m·s-1and 42.7°, respectively. When the visibility ranges between 1000 m and 10000 m, the wind lidar's detection capability varies with the water vapor content in the atmosphere. In cases where relative humidity is below 90%, meeting the criteria for hazy days, the decrease in atmospheric visibility is primarily due to increased aerosol particle content. Under these conditions, the average maximum detection height remains stable above 1200 m. The correlation coefficients for horizontal wind speed and direction are as high as 0.97 and 0.98, with root mean square errors of about 1.1 m·s-1 and 22.3°, respectively. These results are comparable to the detection capability demonstrated under high visibility weather conditions. As relative humidity increases, the impact of water vapor attenuation on laser transmission starts to affect the detection height and accuracy of the wind lidar to varying degrees. When the relative humidity exceeds 95%, the average maximum detection height influenced by water vapor decreases to below 400 m. The correlation coefficient of wind speed decreases to 0.94, with a corresponding increase in the root mean square error to 1.5 m·s-1, and the accuracy of wind direction remains relatively stable under these conditions.